Large animal internal medicine - Smith, Bradford P.
Large Animal Internal Medicine, 5th Edition features a problem-based approach to the diagnosis and management of disease in horses, cattle, sheep, and goats. It offers discussions of over 150 clinical signs and manifestations, as well as comprehensive coverage of laboratory and diagnostic testing. Thoroughly revised and updated content includes new vaccines and vaccination protocols; the most current laboratories for DNA, genetic, and PCR testing; and colostrum supplements and replacers. It's everything you need to stay up to date with the latest information on preventing and treating disease in large animals